2011
DOI: 10.1016/j.foodchem.2010.06.067
|View full text |Cite
|
Sign up to set email alerts
|

Micro-oxygenation and oak chip treatments of red wines: Effects on colour-related phenolics, volatile composition and sensory characteristics. Part I: Petit Verdot wines

Abstract: a b s t r a c tIn this paper, the effects of micro-oxygenation before malolactic fermentation and oak chip treatments on Petit Verdot red wines have been evaluated. Our attention was focused on the colour characteristics, the phenolic compounds related to the colour of red wine, the volatile compounds, and the sensory characteristics of the wines. The micro-oxygenation treatment promoted the stabilisation of red wine colour by increasing the formation of colour-related phenolic compounds (higher concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 40 publications
4
40
0
3
Order By: Relevance
“…Anthocyanins, anthocyanin-related red pigments, and polymeric tannins were affected by preservative treatments whether or not MOx was being applied (Table 3). A decrease of all native free anthocyanins with MOx was detected in agreement with previous results (Cejudo-Bastante et al 2011a, Gambuti et al 2013. For each native anthocyanin the relative loss followed the order: MLL>MLH>MHL>MHH.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Anthocyanins, anthocyanin-related red pigments, and polymeric tannins were affected by preservative treatments whether or not MOx was being applied (Table 3). A decrease of all native free anthocyanins with MOx was detected in agreement with previous results (Cejudo-Bastante et al 2011a, Gambuti et al 2013. For each native anthocyanin the relative loss followed the order: MLL>MLH>MHL>MHH.…”
Section: Resultssupporting
confidence: 92%
“…Additionally, compared to MHH, vitisin B was increased by about 20% in MLL and MLH wines, likely due to the increased formation of acetaldehyde in these wines. In concurrence with these results, Cejudo-Bastante et al (2011a) showed that an oxygen addition increased the concentrations of anthocyanin-ethylflavan-3-ols, anthocyanin-ethyl-B-type-procyanidins, and B-type vitisins, in particular just after the MOx treatment. In addition, the MOx treatment resulted in an increase in polymeric pigments and tannins, and the presence of preservatives limit their formation in agreement with observations of Bakker et al (1998), showing a clear effect of SO 2 on the polymerization processes.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Seguramente la participación de los antocianos en las reacciones con los taninos, favorecidas por la adición de oxígeno, sea la responsable de la disminución del número de estas uniones en los vinos microoxigenados. Cejudo-Bastante et al (2011), estudiando el efecto de la micooxigenación y de la adición de chips sobre la composición fenólica y las características sensoriales de vinos de Petit Verdot, observaron como el color debido a la copigmentación presenta valores superiores en los vinos no microoxigenados, después de la aplicación de oxígeno, una vez finalizada la fermentación maloláctica y posteriormente al contacto del vino con los chips. Además observa como aquellos vinos microoxigenados presentan valores más elevados del color que corresponde a polimerizaciones.…”
Section: Efecto De La Microoxigenaciónunclassified